Nanoimprinting of copper - Goh, Peng Hau (2019)
Controlled fabrication of one-dimensional metallic nanostructures has been of importance as various properties can be tailored for specific applications, through the geometrical customisation of these structures. For example, the hydrophobic characteristic of a surface can be enhanced with high aspect ratio nanostructures. To capitalise on this prospect, numerous nanofabrication methods have been developed to better control the geometry of these nanostructures. However, they are limited by high costs, long fabrication times, inconsistencies and low aspect ratios. Thus, this project explores the viability of using ultrasonic embossing for direct metal nanoimprinting process, in particular, to fabricate copper nanowires for hydrophobic surfaces. Ultrasonic embossing exploits high frequency, low amplitude mechanical vibrations to extrude nanowires in a template-based, single-step process. With the addition of lubrication, such as C60 fullerene, copper nanowires of up to 10µm were successfully fabricated. Moreover, the hydrophobicity of copper surfaces has increased with higher aspect ratio nanowires. The successful fabrication and hydrophobic performance of the copper nanowires were found to be dependent on the embossing amplitude and force parameters.